Hepatitis B induced fulminant liver failure: A call for prevention (Indian Journal of Case Reports, 2024)
Acute fulminant hepatic failure is a condition in which a healthy liver deteriorates rapidly following an insult, resulting in the impairment of its synthetic functions. This condition is rare and is associated with high fatality rates. We report the case of a 19-year-old male who was brought to the emergency room in an unconscious state with jaundice and persistent fever for 2–3 weeks after recently commencing intravenous use of morphine. He was found to be hepatitis B surface antigen reactive, and his laboratory tests indicated severe liver dysfunction with elevated levels of serum bilirubin, aspartate transaminase, alanine transaminase, gamma-glutamyl transferase, and International normalized ratio. The patient was diagnosed with fulminant liver failure with coagulopathy and hepatic encephalopathy. The patient’s family was addressed and counseled regarding the urgent need for liver transplantation. However, due to a lack of funds and insurance, supportive treatment was the only option left. Despite all supportive measures, the patient expired within 48 h. This case highlights the importance of various socioeconomic issues involved with liver transplantation, as in a resource-limited setting, urgent transplantation seems nearly impossible. In addition, this case report raises certain ethical issues that need consideration, particularly in an injection drug use scenario. It also highlights the importance of addressing the rising issue of injection drug use among youth, particularly in the regions of Punjab.